Characterization of fiber matrix interface of continuous‐discontinuous fiber reinforced polymers on the microscale. Issue 1 (18th November 2019) - Rohrmüller, Benedikt; Schober, Michael; Dittmann, Kerstin; Gumbsch, Peter; Hohe, Jörg
Abstract: In lightweight constructions fiber reinforced polymers are an important material group. They combine low density with high strength and stiffness. The characterization of fiber reinforced polymers includes the characterization of the fibers, the matrix and the intermediate interface. The fibers and the matrix can be characterized on the neat materials. Single fiber tests are typically used to characterize the interface. However, the interaction between different fibers inside a composite is not taken into account in a single fiber test. The investigated sheet molding compound (SMC) has a bundle arrangement of the fibers, where the contact of different fibers is very close and therefore also the fiber‐fiber interaction has a high influence. Here we investigate the micromechanical behavior of hourglass shaped micro specimens with several hundreds of fibers with quasi‐static tensile tests. For the interface characterization the microstructure of the specimens is rebuilt in a simulation. The glass fibers are modeled as linear elastic, the matrix as hyperelastic and the interface by means of a cohesive zone model.